INCREASING CREATIVITY THROUGH COLORFUL PLASTICINE PLAYING ACTIVITIES IN GROUP B AT TK TAMAN INDRIA 01 MALANG - Prahesti, Diajeng Anisa; Kustiawan, Usep; Tirtaningsih, Munaisra Tri (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
One of the aspects that can be optimized in early childhood development is creativity in the field of fine arts. Because of this, the researchers chose playing activities using colored flour plasticine media. Apart from being easy to shape the media as desired, this colored flour plasticine media attracts attention with its varied colors, affordable base material prices, and easy to find. This research is a form of Classroom Action Research (PTK) which is processed quantitatively. The data source was taken from group B children for the 2020/2021 school year at Taman Indria 01 Malang Kindergarten, a total of 18 children. The research data is based on the observation sheet instrument. This research is divided into 2 cycles, the first cycle produces an average value of 41.65% and the second cycle produces an average value of 80.55%. Based on the results of the research that has been carried out, it shows that there is an increase in the quality of learning and creativity of group B children in TK Taman Indria 01 Malang.